The Impact of the US Financial Crisis on How Students Pay for College - Hauptman, Arthur M. (International Higher Education, 2009)
The 2008 failure of major financial institutions in the United States may have dramatic ramifications on American students and whether/where they attend college. Several sources of funding may be at risk, including potential decreases in federal financial aid, the tightening of private loan availability, lowered home values impinging on equity-based lending, and stock market losses in college-fund savings. Public institutions, whose tuition is much lower than private or for-profit institutions, may see an increase in enrollment.